2020
DOI: 10.1108/md-05-2019-0581
|View full text |Cite
|
Sign up to set email alerts
|

Organizational injustice and knowledge hiding: the roles of organizational dis-identification and benevolence

Abstract: PurposeWith a basis in social identity and equity theories, this study investigates the relationship between employees' perceptions of organizational injustice and their knowledge hiding, along with the mediating role of organizational dis-identification and the potential moderating role of benevolence.Design/methodology/approachThe hypotheses were tested with three-wave survey data collected from employees in Pakistani organizations.FindingsThe experience of organizational injustice enhances knowledge hiding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 82 publications
3
78
1
1
Order By: Relevance
“…A final limitation pertains to the selection of a moderating variable. As this study was conducted in Pakistan, contextual factors such as the perceived threat to terrorism, law and order situation or perceived organizational injustice might also influence the psychological well-being of employees working in Pakistan (Jahanzeb et al , 2020; Sarwar et al , 2020). Future studies could consider the moderating role of such external factors in the relationship between employee psychological well-being, affective commitment and job performance.…”
Section: Discussionmentioning
confidence: 99%
“…A final limitation pertains to the selection of a moderating variable. As this study was conducted in Pakistan, contextual factors such as the perceived threat to terrorism, law and order situation or perceived organizational injustice might also influence the psychological well-being of employees working in Pakistan (Jahanzeb et al , 2020; Sarwar et al , 2020). Future studies could consider the moderating role of such external factors in the relationship between employee psychological well-being, affective commitment and job performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, Anaza and Nowlin (2017) provided empirical evidence on the negative impact of organizational rewards on knowledge withholding. With regard to issues of knowledge hiding management, although the importance of organizational rewards has been highlighted in many studies (Kumar Jha and Varkkey, 2018;Jahanzeb et al, 2020), several scholars take a different view. Xia et al (2019) indicated that if managers depend solely on organizational rewards to motivate knowledge transfer, organizations may encounter severe knowledge hiding problems.…”
Section: Rq1 Do Financial and Nonfinancial Rewards Have Differential Effects On Employees'mentioning
confidence: 99%
“…In today's highly competitive environment, employees' knowledge-hiding behavior is a prime threat to the growth of contemporary firms (Jahanzeb et al, 2020). Knowledge hiding is defined as an individual's intentional behaviors of withholding or concealing knowledge that has been requested by another individual (Connelly et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, perceived organizational injustice may manifest in convictions that some organizational members receive favourable treatment because they are friendly with the boss or receive credit for doing more than they actually do (Hodson et al, 1994). Beliefs about organizational injustice are stressful for employees, because the unfair treatment drains their resources and may compromise their job functioning and career prospects (Dahling, 2017;Jahanzeb et al, 2020).…”
Section: Introductionmentioning
confidence: 99%